PENGARUH KATALIS NiO DAN NiOMoO TERHADAP PERENGKAHAN MINYAK CANGKANG BIJI JAMBU METE - Lisna Efiyanti; Darma Santi (BRIN Publishing, 2016)
Bioenergy is new and renewable alternative energy which is currently developed enthusiastically. Bioenergy could be produced by catalytic cracking method, which is cracking carbon chain to raise energy fraction. This paper observes potential non-food bioenergy of cashew nut shell liquid as an alternative bioenergy source using catalytic cracking method. The effect of impregnated-metals Nikel and Molibdenum catalyst used in hydrocracking of Cashew Nut Shell Liquid (CNSL) into bioenergy was investigated. It focused specifically on two type of natural activated zeolite catalysts: NiO and NiOMoO at temperature reaction of 450 C and ratio feed catalyst of 2 and 4. Catalysts characterization was conducted according to a gravimetric method to determine acidity of catalyst; Spectroscopy FT-IR analysis to get distribution of active site catalyst; X-Ray Diffraction (XRD) analysis to observe crystalinity of catalyst; and Gas Sorption Analyzer (GSA) to measure surface area, porosity and total of pore volume. Bioenergy of CNSL in the liquid-phase, which were predominantly by gasoline, diesel oil, and heavy oil, was further analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) to determine the compound energy fraction qualitatively and quantitatively. The result showed that the NiOMoO (natural activated zeolite) provided an optimal performance with liquid product conversion was about 65-75%, and selectivity gasoline as well as diesel fraction was about 37-47% and 22-31%, respectively.